A Liouville Property of Holomorphic Maps. (15th May 2013) - Yu, Chengjie
Abstract : We prove a Liouville property of holomorphic maps from a complete Kähler manifold with nonnegative holomorphic bisectional curvature to a complete simply connected Kähler manifold with a certain assumption on the sectional curvature.